BUDGET EFFICIENCY AND DIGITALIZATION READINESS IN STREGTHENING LOCAL GOVERNMENT HUMAN RESOURCES - Tirza Haqia Purnama; Roni Ekha Putera; Tengku Rika Valentina (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Budget efficiency and accelerated digitalization are urgent demands for local governments. However, the low digital competence of human resources and bureaucratic resistance reveal the paradox between policy ambition and implementation reality. An efficiency approach without investment in human capacity has the potential to produce pseudo-digitalization that is only sophisticated on the surface but fragile in practice. Therefore, a long-term transformative strategy is needed that can strengthen the foundations of local governance in real terms. This research aims to examine how budget efficiency and digitization initiatives can be directed towards strengthening human resources within local governments. The main focus lies on how fiscal efficiency policies and the use of information technology can be aligned with the need to improve competencies, work culture, and supporting institutions. The method used is literature study and policy analysis by reviewing relevant official documents, regulations, and results of previous studies. The study was conducted thematically by identifying good practices and common obstacles in the implementation of digitization oriented towards strengthening human resources. The theoretical framework used includes the theory of organizational innovation adoption and the institutional capacity approach in public management. The results show that digitization based budget efficiency will only have a positive impact if followed by a structured apparatus capacity building strategy. Cultural resistance and lack of transformational leadership are the main obstacles. In contrast, local governments that make digitalization part of HR development are able to increase efficiency while encouraging sustainable organizational change. This research underscores the importance of alignment between fiscal efficiency policies, technological readiness, and investment in human capacity as the key to successful bureaucratic transformation in the digital era.